Exploring the barriers and facilitators to volunteering as an intervention for those with long‐term neurological conditions: How make therapeutic volunteering possible? - Helene Eisenhut; Johnny Collett; Farzaneh Yazdani (Wiley, 2024)
Abstract Background Volunteering may have therapeutic benefits, but little is known about its requirements and potential for people with neurological conditions (pwNC). Design Two separate focus groups were conducted in Darmstadt, Germany: one group consisting of six pwNC and another group consisting of four health care professionals and three volunteering service providers. The focus groups were audio‐recorded, transcribed and data were managed using NVivo12. The thematic analysis was applied. Results Four main themes were identified: (1) Impact of volunteering, (2) Individualisation, (3) Developmental space and (4) Funded supported volunteering. Conclusion According to the findings, volunteering can be used as a strategy to enhance physical, mental and social well‐being in disease management for people with long‐term neurological conditions. Patients or Public Contribution Facilitators for accessibility of therapeutic volunteering; involvement of pwNC.